Kajian Etika Kristen tentang Prinsip Mengasihi berdasarkan Kitab Injil dan Implikasinya bagi Orang Kristen - Harefa, Info Krisdamai; Malik Bambangan (Tumou Tou, 2024)
The aim of this research is to identify and analyze the teachings of love in the Bible, as well as understand how these principles are applied in the daily lives of Christians. The research method used is a qualitative method with a hermeneutic approach to interpreting the texts of the Gospels. Data analysis was carried out by emphasizing the historical and cultural context of the texts of the Gospels, as well as reflection on the relevance of the teachings of love in facing the challenges of the modern era. This research updates the study of Christian ethics by highlighting the relevance and challenges in implementing the principles of love in the contemporary era, as well as offering practical guidance for Christians to realize love in real daily actions, both in personal and community relationships. Thus, this article contributes to a deeper and more applicable understanding of the teachings of love in the Bible, as well as providing new insights for Christians in living the values of love in various aspects of life.